Sickle Cell Disease Treatment with Arginine Therapy (STArT): study protocol for a phase 3 randomized controlled trial - Chris A. Rees; David C. Brousseau; Daniel M. Cohen; Anthony Villella; Carlton Dampier; Kathleen Brown; Andrew Campbell; Corrie E. Chumpitazi; Gladstone Airewele; Todd Chang; Christopher Denton; Angela Ellison; et al. (Trials, 2023)
Abstract Background Despite substantial illness burden and healthcare utilization conferred by pain from vaso-occlusive episodes (VOE) in children with sickle cell disease (SCD), disease-modifying therapies to effectively treat SCD-VOE are lacking. The aim of the Sickle Cell Disease Treatment with Arginine Therapy (STArT) Trial is to provide definitive evidence regarding the efficacy of intravenous arginine as a treatment for acute SCD-VOE among children, adolescents, and young adults. Methods STArT is a double-blind, placebo-controlled, randomized, phase 3, multicenter trial of intravenous arginine therapy in 360 children, adolescents, and young adults who present with SCD-VOE. The STArT Trial is being conducted at 10 sites in the USA through the Pediatric Emergency Care Applied Research Network (PECARN). Enrollment began in 2021 and will continue for 5 years. Within 12 h of receiving their first dose of intravenous opioids, enrolled participants are randomized 1:1 to receive either (1) a one-time loading dose of L-arginine (200 mg/kg with a maximum of 20 g) administered intravenously followed by a standard dose of 100 mg/kg (maximum 10 g) three times a day or (2) a one-time placebo loading dose of normal saline followed by normal saline three times per day at equivalent volumes and duration as the study drug. Participants, research staff, and investigators are blinded to the participant’s randomization. All clinical care is provided in accordance with the institution-specific standard of care for SCD-VOE based on the 2014 National Heart, Lung, and Blood Institute guidelines. The primary outcome is time to SCD-VOE pain crisis resolution, defined as the time (in hours) from study drug delivery to the last dose of parenteral opioid delivery. Secondary outcomes include total parental opioid use and patient-reported outcomes. In addition, the trial will characterize alterations in the arginine metabolome and mitochondrial function in children with SCD-VOE. Discussion Building on the foundation of established relationships between emergency medicine providers and hematologists in a multicenter research network to ensure adequate participant accrual, the STArT Trial will provide definitive information about the efficacy of intravenous arginine for the treatment of SCD-VOE for children. Trial registration The STArT Trial was registered in ClinicalTrials.gov on April 9, 2021, and enrollment began on June 21, 2021 (NCT04839354).